The Influence of Quizizz Media Within the Team Games Tournament (TGT) Learning Approach on the Achievement of Fiqh Learning Outcomes Among Tenth-Grade Students at MA Masalikil Huda - Kusmaidah Kusmaidah; Ahmad Saefudin (Action Research Journal Indonesia (ARJI), 2025)
This study aims to analyze the effect of using Quizizz media within the Team Games Tournament (TGT) learning approach on improving students’ learning outcomes in the Fiqh subject among tenth-grade students at MA Masalikil Huda. Specifically, the objectives of this research are: (1) to explain how the implementation of Quizizz can enhance student interaction and engagement during the learning process, and (2) to examine the extent to which the TGT method influences students’ academic achievement. The research employed a quantitative approach with a quasi-experimental design, involving two evaluation stages: pretest and posttest. Data were collected through learning achievement tests and analyzed using the Paired Sample t-Test and simple linear regression test with the assistance of IBM SPSS Statistics 26. The results revealed a significant difference between pretest and posttest scores, with an increase in the average learning outcome from 72 to 80 and a significance value of 0.014 < 0.05. These findings demonstrate that the integration of Quizizz media within the TGT method effectively enhances students’ understanding, motivation, and active participation in Fiqh learning. The implications of this study emphasize the importance of adopting technology-based and collaborative learning innovations to create more interactive, effective, and meaningful learning experiences within the Islamic educational context.